Die DDR im Bild : zum Gebrauch der Fotografie im anderen deutschen Staat - Hartewig, Karin 1959- HerausgeberIn; Lüdtke, Alf 1943-2019 HerausgeberIn (Wallstein Verlag, 2004)
Zum Gebrauch der Fotografie im anderen deutschen Staat